PENINGKATAN KEPEDULIAN DIRI SISWA MELALUI SOSIALISASI PERGAULAN SEHAT DI SMAN 3 LUWU UTARA - Permadi Kusuma; Nirsal (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Unhealthy social interactions among adolescents can have a negative impact on students’ social behavior, mental health, and self-care. This situation underscores the need for educational activities as a preventive measure to foster positive social behavior within the school environment. This community service activity aims to improve students’ self-care through the promotion of healthy social interactions at SMAN 3 Luwu Utara. The activity was implemented through stages of preparation, presentation of material, interactive discussion, Q&A, and evaluation. The material covered included the definition of healthy social interactions, the impact of negative social interactions, the importance of maintaining mental and social health, and the wise use of social media. Evaluation was conducted through observation and the distribution of questionnaires to assess participants’ level of understanding following the activity. The activity was attended by 25 students. The evaluation results showed an increase in participants’ average scores from 65.2 on the pre-test to 77.6 on the post-test, representing an increase of 12.4 points (19.02%). These findings indicate that the socialization method combined with interactive discussions is effective in improving students’ understanding of the importance of maintaining healthy social relationships, fostering self-care, maintaining mental health, and using social media responsibly. It is hoped that this activity can serve as a preventive measure in shaping positive character and behavior among adolescents in the school environment.